A Programme of College Education for Mothers with Small Children: An Evaluation of its Effects on Mental Health - Kiely, Margaret C. (Canadian Journal of Counselling and Psychotherapy, 2012)
An innovative programme in education and mental health for mothers (largely middle class) of pre-school children has been established by Marianopolis College in Montreal, in collaboration with the Mental Hygiene Institute. Many young mothers feel alienated from a rapidly changing society and would like to return to their studies but the difficulties inherent in such a step prevent most from doing so. Aware of these feelings of stress, frustration, and alienation, the College established a programme whereby the women could attend classes during the morning hours and bring their children with them to the free nursery school on campus, which was organized specifically for this purpose. Some courses were offered to the women as a group, thus lessening the tension of attending classes alone with much younger students. Evaluation of the first year of the project revealed that these women were capable of integrating their roles of wife, mother, and student; had achieved a sense of competence enabling them to pursue further studies individually; and for the most part, were now able to choose an occupational goal. In future it is intended to extend the programme so that mothers of lower socio-economic levels could avail themselves of this same opportunity.